BENTHIC HARMFUL DINOFLAGELLATE ASSEMBLAGES IN A FRINGING REEF OF SAMPADI ISLAND, SARAWAK, MALAYSIA - Tan, Toh-Hii; Lim, Po-Teen; Mujahid, Aazani; Usup, Gires; Leaw, Chui-Pin (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 2013)
A study on the presence and relative abundance of benthic harmful algal bloom (BHAB) forming dinoflagellate species was carried out in the coral reefs of Sampadi Island, Sarawak, Malaysia. The study involved deployment of fiberglass screens as an artificial substrate for the benthic epiphytic microalgae. The screens were placed for 24 h above the seafloor along a 100 m transect at 10 m intervals. BHAB species attached to the screens were identified and cell abundances were enumerated under a light microscope. The BHAB community at the study site was dominated by Prorocentrum spp. and Coolia spp. Other BHAB species collected included Amphidinium spp., Gambierdiscus spp. and Ostreopsis spp. Total cell densities collected on the screens ranged from 5 to 100 cells per 100 cm2. The two BHAB groups of primary concern, Gambierdiscus spp. and Ostreopsis spp. were detected at relatively low abundances of 0.6â??4.2% and 1.8â??16% respectively. This study has shown that potentially toxic BHAB species were present in the coral reef and the artificial substrate approach could provide a convenient quantitative method for the collection of clean samples for identification and enumeration purposes.